2000
DOI: 10.1021/np990567x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Lavandulyl Flavanones from Sophora flavescens

Abstract: Two new lavandulylated flavanones, (2S)-2'-methoxykurarinone (1) and (-)-kurarinone (2), were isolated from the root of Sophora flavescens, together with two known lavandulyl flavanones, sophoraflavanone G (3) and leachianone A (4), and two known isoflavonoids, formononetin and l-maakiain. The structures of 1 and 2 were determined on the basis of optical rotation and spectral evidence and by comparison with known compounds. Compounds 1-4 exhibited cytotoxic activity against human myeloid leukemia HL-60 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
78
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 10 publications
4
78
0
Order By: Relevance
“…We report here the isolation and the structure elucidation of a flavanone, naringenin 5-methyl ether (1), a flavanone glycoside, pinocembrin-7-glycoside (2) and vomifoliol (3) from the ethyl acetate aerial part extract of Echiochilon fruticosum. The structures were established on the basis of 2D NMR spectroscopic experiments and by comparison of the NMR data with literature values [7][8][9][10]. (Table I) with those of the literature [7][8] thus confirmed the S-configuration of C 2 .…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…We report here the isolation and the structure elucidation of a flavanone, naringenin 5-methyl ether (1), a flavanone glycoside, pinocembrin-7-glycoside (2) and vomifoliol (3) from the ethyl acetate aerial part extract of Echiochilon fruticosum. The structures were established on the basis of 2D NMR spectroscopic experiments and by comparison of the NMR data with literature values [7][8][9][10]. (Table I) with those of the literature [7][8] thus confirmed the S-configuration of C 2 .…”
Section: Introductionmentioning
confidence: 55%
“…The structures were established on the basis of 2D NMR spectroscopic experiments and by comparison of the NMR data with literature values [7][8][9][10]. (Table I) with those of the literature [7][8] thus confirmed the S-configuration of C 2 . H-NMR spectrum with that of 1 (Table I) permitted us to note on the one hand, the presence of all proton signals of 1 with the exception of that of the methoxyl group at 3.82 ppm, and on the other, one additional signal at δ 7.39 (m, H 4' ).…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…The root of S. flavescens is an oriental herbal medicine, used as a diuretic and for the treatment of jaundice, leucorrhea, carbuncles, pyogenic infections of the skin, scabies, enteritis, and dysentery. Recently, biological and pharmacological studies have revealed anti-inflammatory, 12) and antitumor, 13) antioxidant 14) for the crude extracts or isolated constituents of S. flavescens. In particular, MK, the main component of S. flavescens, was reported that had the antioxidant activity, it results in the down-regulation of glutamate-induced neurotoxicity via the induction of heme oxygenase-1 (HO-1).…”
mentioning
confidence: 99%
“…Sophora flavescens, a leguminous plant, produces diverse 8-lavandulylated flavanones, such as sophoraflavanone G (SFG), kurarinone and kushenol I (Hatayama and Komatsu 1971;Wu et al 1985;Kuroyanagi et al 1999;Kang et al 2000), which are exclusively accumulated in the cork layer of intact roots (Yamamoto et al 1992). Recent pharmaceutical studies showed that the lavandulyl side chain was essential for the antitumor activity and phospholipase-Cg1-inhibition activity of flavonoids isolated from this plant, and that SFG had the most potent activities (Lee et al 1997;Ko et al 2000).…”
mentioning
confidence: 99%